Effect of some disinfectant solutions on the hardness property of selected soft denture liners after certain immersion periods. - Hussein, Basima M.A.; Ismail, Intisar J.; Khalaf, Hanan A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Disinfection of denture and soft denture liners became among the priorities for cross contamination control as well as patient’s health. All the trials aimed to have maximum infection control with minimal adverse changes in the materials properties. Materials and methods: Discs of 30x2mm were made from Coe Super Soft and Coe Soft denture liners. Every 5 specimens were immersed separately and daily in CHX, Sodium hypochlorite and chlorine dioxide, control group specimens were immersed in the distilled water. Hardness property of the experimental and control groups was evaluated by using Shore A durometer after 1, 7, 30 days. Results: Statistical analysis indicated non significant differences when the control group was compared with every disinfectant solution regarding tested periods, while ANOVA test showed significant differences among tested solutions after every testing period. Further LSD attributed these differences to the chlorine dioxide since it is the only solution that decreases hardness value after immersion. Conclusion: Either of the tested solutions can be used safely regarding hardness property, although CHX and Sodium hypochlorite are more recommended since their effects on the hardness property was relatively same in comparison to the control.